Xian dai xi ju xuan - Dai, Zhongfang; Hu, Nanxiang (Zhong xue guo yu bu chong du ben., 1934)
Shou Tian Han, Ding Xilin, Zhen boqi, Hong Shen, Ouyang Yuqian, Xiong Foxi, Liu Dajie, Yuan Muzhi, Ma Yanxiang, Gu jianchen deng ren de duan ju 12 pian.